Transforming CT-Scan Scheduling System in Hospital Through Web-Based Technology - Hayati, Nur; Sudiyono, Sudiyono; Handoko, Bagus Dwi; Budiati, Tri Asih; Kartikasari, Yeti; Wibowo, Gatot Murti (Universitas Muhammadiyah Yogyakarta, 2024)
The schedule for outpatient CT-Scan examinations at Bhayangkara Level I Hospital is encountered with problems, including recording errors due to poor patient manual scheduling and service delays. These challenges have been a great disadvantage to health workers and administrative systems, impacting the quality of health service. A web-based application, “SIJARO-CT,” in integration with the Hospital Health Management Information System (SIMRS), was designed and assessed to solve this problem. The method used for this study was R&D), which also placed emphasis on the ISO 9126 standard for system quality evaluation and its efficiency with regard to resources, time, cost, and quality of functional services. The results show that the system validation was rated 100% in the excellent range, which substantially improved resource use and quality of services (p=0.003). The study points out that even though the system potentially improves operational performance, its weaknesses include the single site implementation and limited scale as it shows quite room for further exploration. This research adds value to the healthcare sector through operationalizing, optimizing hospital management, and integrating these systems across levels to increase efficiency, service delivery, and satisfaction in healthcare sector institutions operating in a variety of contexts.